The Influence of Transformational Leadership Style on Job Satisfaction and Organizational Commitment - Tiara Puspa; Retno Sari Murtiningsih; Adella Cirealkita; Adillah Dzata Amani; Ghea Dwi Fuzi Lestari; Tyas Widyanti (Telaah Bisnis, 2019)
Abstract The purpose of this research was to analyze the influence of Transformational Leadership Style on Job Satisfaction and Organizational Commitment. The design of this research used primary data obtained by distributing questionnaires to 147 respondents, the employees of the State Gas Company located in Jakarta. Stratified Sampling Sample was used and data were analyzed by using Statistical Package for Social Sciences (SPSS). The method used to analyze data were Descriptive Statistic Method and Multiple Regression. From the result of this research, it can be concluded that there was a positive relationship between organizational commitment and transformational leadership, as well as a positive relationship between transformational leadership and job satisfaction.